Strategi Perencanaan Purchasing Department Pada Masa Pandemi Covid-19 : Studi Kasus Pada Hotel 1o1 Urban Pemuda Jakarta - Fitrani, Dina; Nugraha, Rizki Nurul; Azzahra, Febry Fatimah; Methania, Ribka; Sukowati, Sifa (Peneliti.net, 2023)
The COVID-19 pandemic is a challenge for almost every industry, especially the tourism industry consisting of hotels, restaurants, and so on. One Department that must play an important role in the midst of this condition is the Purchasing Department. The purpose of this study is to find out how the Purchasing Department can survive during the Covid-19 pandemic in regulating procurement. This type of research is qualitative descriptive research through an interview approach with the Purchasing Department. Some of the steps taken by the Purchasing Department in procurement during the pandemic are in-depth evaluation of goods needs, use of local alternatives, monitoring stock of goods, good communication with suppliers, implementing emergency procurement policies, utilising digital technology and solutions, and monitoring compliance with health and safety protocols.